Предмет: Алгебра,
автор: bvzii901
Упростите выражение b(b+c)-(b+c)2
Выберите один ответ:
-3bc+c2
3bc+c2
-bc-c2
2b2-bc-c2
Ответы
Автор ответа:
2
b(b + c) - (b + c)² =b² + bc - b² - 2bc - c² = - bc - c²
Автор ответа:
2
Ответ:
-bc-c2
Объяснение:
b(b+c)-(b+c)2 = b2+bc-b2-2bc-c2 = -bc-c2
Похожие вопросы
Предмет: Русский язык,
автор: наил1
Предмет: Русский язык,
автор: знаток5555
Предмет: Қазақ тiлi,
автор: ariannawhale
Предмет: Математика,
автор: ДайОтвет2281
Предмет: Английский язык,
автор: krasnovatany201